Treinamento resistido e educação física: uma análise da produção do conhecimento nos periódicos da área no período de 2000 à 2019 - PINTO, Luã Amaral (2022)
Physical education is an area of knowledge that presents several fields of activity, these can be decomposed between the school field and the non-school field. In this sense, we seek to discuss the theme of knowledge production regarding resistance training. Thus, we look at the texts produced and published in 5 major journals in the area of physical education: RBCE, Motriexperience, Movement, Motive and Thinking practice in the period from 2000 to 2019, which correspond to 19 years of scientific production. The general objective of the research is to analyze the panorama of knowledge production on the theme of resistance training in the journals in the area of physical education from 2000 to 2019. It was concluded that in the journals studied the productions on resistance training, they are incipient despite the numerous benefits that are highlighted on resistance training and health. In this sense, expanding studies on the subject is necessary. It is necessary to discuss the production of knowledge in the area of resistancetraining in order to expand discussions and research on the subject in Theses, Dissertations, journals of the area and other spaces, emphasizing the social value that these research has for the population.